Gastrin releasing peptide and gastrin releasing peptide receptor expression in gastrointestinal carcinoid tumours. Issue 2 (27th January 2004) - Scott, N; Millward, E; Cartwright, E J; Preston, S R; Coletta, P L
Abstract : Aims: To establish whether gastrin releasing peptide (GRP) and the GRP receptor (GRPR) are expressed together in gastrointestinal carcinoid tumours. Methods: Twenty six carcinoid tumours from the stomach, small intestine, appendix, and colorectum were investigated by immunohistochemistry for GRP and GRPR. Results: GRP was detected in nine of 19 tumours and GRPR in 22 of 26. Coexpression of both the ligand and receptor was seen in six of 19 cases. GRPR but not GRP was more strongly expressed in appendix and colonic tumours. Conclusions: GRP and GRPR are produced by a large number of gastrointestinal carcinoid tumours. An autocrine/paracrine pathway may exist for GRP stimulated cell proliferation in some of these neoplasms, analogous to that seen in small cell anaplastic carcinoma of the lung.